2016
DOI: 10.1590/0102-33062016abb0048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest structure on litter production, soil chemical composition and litter-soil interactions

Abstract: Litter production in forest ecosystems is a major indicator of primary productivity because litter helps incorporate carbon and nutrients from plants into the soil and is directly involved in plant-soil interactions. To our knowledge, few studies have investigated the relationship between species diversity and ecosystem processes in subtropical forest fragments. In this work, we determined forest structural parameters and assessed seasonal leaf litter input, leaf decomposition rate, litter quality and soil cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 42 publications
0
15
1
4
Order By: Relevance
“…As espécies avaliadas pertencem as famílias Myrtaceae e Fabaceae, consideradas as mais representativas em fragmentos florestais subtropicais, com importantes serviços ecossistêmicos (Capellesso et al 2016, Oliveira et al 2017, Capellesso et al 2018. A alta riqueza e abundância destas famílias em fragmentos florestais subtropicais podem estar associadas com a capacidade em enfrentar diferentes filtros ambientais, incluindo os períodos frequentes de saturação hídrica do solo, alternados com períodos de seca, além dos regimes de luminosidade.…”
Section: Discussionunclassified
“…As espécies avaliadas pertencem as famílias Myrtaceae e Fabaceae, consideradas as mais representativas em fragmentos florestais subtropicais, com importantes serviços ecossistêmicos (Capellesso et al 2016, Oliveira et al 2017, Capellesso et al 2018. A alta riqueza e abundância destas famílias em fragmentos florestais subtropicais podem estar associadas com a capacidade em enfrentar diferentes filtros ambientais, incluindo os períodos frequentes de saturação hídrica do solo, alternados com períodos de seca, além dos regimes de luminosidade.…”
Section: Discussionunclassified
“…The higher total annual litterfall in the Mata Alta was a result of the more robust structure of that phytophysiognomy, which, in turn, led to the differences between the areas in terms of primary productivity (Capellesso et al, 2016) related to their contrasting edaphic characteristics. The soil in the Mussununga area is sandy and nutrient-poor when compared to the Mata Alta soil (Garay et al, 1995) due to cation leaching.…”
Section: Fine Litterfallmentioning
confidence: 99%
“…Dominant canopy species, especially adult tree individuals, occupy a large proportion of biomass, in both temperate and tropical forests (Hu et al 2015;Wu et al 2015;Li et al 2018). Evidently, leaf production shows strong correlation with tree biomass (Baishya and Barik 2011;Poorter et al 2012;Zhang et al 2015), and therefore, trees with high biomass produce a large amount of leaf litter input (Nouvellon et al 2012;Capellesso et al 2016). Earlier, some studies have reported that dominant tree species litter could significantly affect spatial soil nutrient heterogeneity in temperate ecosystems (Suo et al 2016) and northern hardwood forests (Bigelow and Canham 2015).…”
Section: Introductionmentioning
confidence: 99%